Kisspeptin: new biomarker of pregnancy - Meena, Priyanka; Mathur, Rati; Meena, Mohan L. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The recently identified hormone kisspeptin has been suggested to play an important regulatory role in placentation. The aim and objective of the study is the measurement of serum kisspeptin level in asymptomatic pregnant women and to find out the association of serum kisspeptin with gestational age in women with early pregnancy. Methods: This was a longitudinal study to the evaluation of 178 asymptomatic pregnant women with a gestation of 6 to 16 weeks attending routine antenatal booking visit recruited as study participants from the Antenatal Clinical of Obstetrics and Gynaecology Department, S.M.S. Medical College and Attached Hospitals, Jaipur, Rajasthan, India. Results: After initial clinical examination of every participant, a single blood sample was taken for the measurement of serum kisspeptin. Serum kisspeptin measurement test was performed by ELISA method and results were expressed as ng/ml. Pregnancy outcome was recorded prospectively. Mean serum kisspeptin level of study participants was 2.80±1.87ng/ml and median were 2.41 (Range 0.244-14.06ng/ml). Our result showed the relationship of serum kisspeptin with gestational age (GA) (p<0.000). Conclusions: serum kisspeptin level increases in pregnancy and showed positive relationship with gestational age significantly (p<0.000).